Beginning jQuery 2 for ASP.NET Developers Using jQuery 2 with ASP.NET Web Forms and ASP.NET MVC - Joshi, Bipin; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
jQuery is the most popular JavaScript library in use today, appearing on nearly two thirds of the 10,000 most visited sites on the web. With this sort of popularity, it’s clear that ASP.NET developers can’t afford to miss out. By combining jQuery with ASP.NET you get the best of both worlds: the client-side interactivity and responsiveness of JavaScript with the robustness and extensibility of Microsoft's web stack. Beginning jQuery 2 for ASP.NET Developers shows you how. To begin with, you'll find out how jQuery hooks up with your ASP.NET controls, and simplifies event handling by keeping it in the browser. Then you'll learn to handle dynamic content and responsive layouts by interacting with the DOM. Effects and animations are one of the most popular uses of the jQuery library, so we cover that next—showing you how to get a sleek modern look and feel to your site using some of the vast library of JavaScript that's already out there waiting to be used. Ajax is one of the areas where jQuery really shines, so you'll find out how to make Ajax calls to a web service and get data onto a page without waiting for slow ASP.NET postbacks every time. And no book on jQuery would be complete without jQuery Mobile: the popular mobile web framework that gets you writing sites that work across all the major mobile platforms.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems